Diseño de un amplificador operacional de transconductancia aplicando técnicas de optimización multiobjetivo - Pereira-Arroyo, Roberto; Molina-Robles, Roberto; Chacón-Rodríguez, Alfonso (Instituto Tecnológico de Costa Rica, 2014)
In this paper, the problem at hand consists in the sizing of an Operational Transconductance Amplifier (OTA). The Pareto front is introduced as a useful analysis concept in order to explore the design space of such analog circuit. A genetic algorithm (GA) is employed to automatically detect this front in a process that efficiently finds optimal parameterizations and their corresponding values in an aggregate fitness space. Since the problem is treated as a multiobjective optimization task, different measures of the amplifier like the transconductance, the slew rate, the linear range and the input capacitance are used as fitness functions. Finally, simulation results are presented, using a standard 0,5μm CMOS technology.
Design of an operational transconductance amplifier applying multiobjective optimization techniques
Artículo de Revista: Tecnología en marcha. Volúmen 27, número 1, (enero/marzo, 2014), páginas 3-12.
Keywords: Algoritmos; Algoritmos genéticos; Pareto; CMOS